2021
DOI: 10.1186/s12889-021-11972-6
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activities and the risk of cardiovascular mortality in the Malmö diet and Cancer study

Abstract: Background The association between leisure-time physical activity and cardiovascular mortality has been previously studied, but few studies have focused on specific activities and intensities. Methods The association between different leisure-time physical activities and cardiovascular mortality was investigated among 25,876 individuals without diabetes or cardiovascular disease from the population-based Malmö Diet and Cancer Study cohort. The indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A decrease in risk for aIS was observed to about a total PA level of approximately 240 MET-hours/week, beyond this threshold no added advantage was observed, and no significant linear trend was seen for total PA level. Similarly, individuals with low leisure-time PA level appeared to be at higher risk, but no significant benefit or harm was seen with higher levels of leisure-time PA. Another study on the same cohort with CVD as endpoint also concluded that those who were physically inactive have the highest reduction in risk (48). A systematic review and dose-response meta-analysis including 26 studies examining different domains of PA and risk of IS found a significant association between higher total PA level and lower risk of IS.…”
Section: Discussionmentioning
confidence: 95%
“…A decrease in risk for aIS was observed to about a total PA level of approximately 240 MET-hours/week, beyond this threshold no added advantage was observed, and no significant linear trend was seen for total PA level. Similarly, individuals with low leisure-time PA level appeared to be at higher risk, but no significant benefit or harm was seen with higher levels of leisure-time PA. Another study on the same cohort with CVD as endpoint also concluded that those who were physically inactive have the highest reduction in risk (48). A systematic review and dose-response meta-analysis including 26 studies examining different domains of PA and risk of IS found a significant association between higher total PA level and lower risk of IS.…”
Section: Discussionmentioning
confidence: 95%
“…This association could be mediated by the impacts of LTPA on individual traditional cardiovascular risk factors [ 53 ]. These impacts may be attributed to the reduced cardiovascular mortality in moderate- and high-intensity LTPA adherents [ 49 , 54 ], and the largest reduction is observed with approximately 300 min of walking per week [ 54 ], largest intensity of LTPA and after 10 years of LTPA behavior [ 50 ]. This amount of LTPA/week translates to approximately 150–300 min/wk of long-term vigorous-intensity LTPA or 300 to 600 min/wk of long-term moderate-intensity LTPA [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 This association could be mediated by the impacts of LTPA on individual traditional cardiovascular risk factors. 51 These impacts may be attributed to the reduced cardiovascular mortality in moderate-and high-intensity LTPA adherents, 47,52 and the largest reduction is observed with approximately 300 minutes of walking per week, 52 largest intensity of LTPA and after 10 years of LTPA behaviour. 48 This amount of LTPA/week translates to approximately 150 to 300 min/wk of long-term vigorous-intensity LTPA or 300 to 600 min/wk of long-term moderate-intensity LTPA.…”
Section: Discussionmentioning
confidence: 99%